Physical deterioration in an acute mental health unit: A quantitative retrospective analysis of medical emergencies. (27th April 2018) - Porter, Joanne E.; Cant, Robyn; Missen, Karen; Raymond, Anita; Churchill, Anne
Abstract: Nursing management of physical deterioration of patients within acute mental health settings is observed, recorded, and actively managed with the use of standardized Adult Deterioration Detection System (ADDS) charts. Patient deterioration may require the urgent assistance of a hospital rapid response or Medical Emergency Team. A five‐and‐a‐half‐year (2011–2016) audit of hospital‐wide Medical Emergency Team attendances was conducted in an acute mental health unit of a single large 250 bed regional hospital in Victoria, Australia. Data were extracted from the hospitals' quality and patient safety program, RISKMan, and entered into a statistical data program for analysis. A total of 140 patient records were analysed, and the 'Worried' category (34%, n  = 47) was the principle reason for a Medical Emergency Team call in a mental health ward, followed by hypotension (23%, n  = 31) and a low Glasgow Coma Score (16%, n  = 22). Upon further investigation of the 'Worried' category, the most common conditions recorded were an altered conscious state (22%, n  = 9), low oxygen saturation (20%, n  = 8), or chest pain (17%, n  = 7). Activation of Medical Emergency Team calls predominantly occurred in the daylight morning hours (6am–12md). When data were compared to the general hospital patients, the context of the physiological deterioration of the mental health patients was strikingly similar. Further research is recommended to ascertain the extent and frequency with which staff working in mental health units are performing vital signs monitoring as an essential component of detection of early signs of physiological deterioration.